Fiasco: The Anglo-Franco-Soviet Alliance That Never Was and the Unpublished British White Paper, 1939–1940 - Carley, Michael Jabara (The International History Review, 2019)
This article is about the Anglo-Franco-Soviet negotiations in 1939 for an alliance against Nazi Germany and about how the British government later tried to represent those negotiations to public opinion. The first part of the essay presents the Soviet point of view on the negotiations and how the British and French governments, though mainly the British, reacted to Soviet alliance proposals. It is a fresh representation of the Soviet perspective from published and unpublished Russian language sources. The second part of the essay focuses on how the British sought to represent the abortive negotiations through a white paper, placing the blame for failure on the Soviet Union. France opposed publication because, however carefully prepared, the white paper showed that the Soviet side had made serious alliance proposals with precise, reciprocal undertakings which the British government was reticent to entertain. The French were all the more annoyed because the white paper omitted to underline that they had been more receptive to Soviet proposals. The trilingual, multi-archival evidence presented in the first part of the essay effectively supports the French perception of the white paper and more generally of the failed tripartite negotiations.
_eprint: https://doi.org/10.1080/07075332.2018.1458043
Keywords: Britain; France; Soviet Union; World War II; appeasement